Clinical Manifestations of Alport Syndrome-Diffuse Leiomyomatosis Patients With Contiguous Gene Deletions in COL4A6 and COL4A5 - Zhou, Xi; Wang, Jingjing; Mao, Jianhua; Ye, Qing (Frontiers in Medicine, 2021)
Alport syndrome-diffuse leiomyomatosis is a rare type of X-linked Alport syndrome resulting from contiguous deletions of 5′ exons of COL4A5 and COL4A6. Studies have suggested that the occurrence of diffuse leiomyomatosis is associated with the characteristic localisation of the COL4A6 gene deletion break point. An electronic database was searched for all studies accessing AS-DL to analyze the clinical characteristics, gene deletion break points of patients with AS-DL, and the pathogenesis of AS-DL. It was found that the proportion of de novo mutations of AS-DL was significantly higher in female probands than male probands (78 vs. 44%). Female patients with AS-DL had a mild clinical presentation. The incidence of proteinuria and ocular abnormalities was much lower in female probands than in male probands, and there was generally no sensorineural hearing loss or chronic kidney disease (CKD), which progressed to Stage 3 in female probands. The contiguous deletion of the 5' exons of COL4A5 and COL4A6, with the break point within the intron 3 of COL4A6, was the critical genetic defect causing AS-DL. However, the pathogenesis of characteristic deletion of COL4A6 that contributes to diffuse leiomyomatosis is still unknown. In addition, characteristic contiguous deletion of COL4A5 and COL4A6 genes in AS-DL may be related to transposed elements (TEs).